Re: Rational equation & Rearranging formula
(x-1)²/(x-2) = 9/2
Multiply by (x-2): (x-1)² = 9/2(x-2)
Expand the brackets: x² -2x +1 = 9/2x - 9
Rearrange into quadratic form: x² -13/2x +10 = 0
Solve: x = 2.5 or 4
(y+2)/(y+1) = x
Rewrite the numerator: (y+1+1)/(y+1) = x
Take out the common factor: 1 + 1/(y+1) = x
Get the y term on its own: 1/(y+1) = x-1
Multiply by y+1: 1 = (x-1)(y+1)
Get the y term on its own: 1/(x-1) = y+1
Make y the subject: y = 1/(x-1) -1
Why did the vector cross the road?
It wanted to be normal.